Perspectives of Water Level Measurement in Plastic Pipes Using Wideband Horn Antenna - Farid, Z.; Najam, Z.; Khan, M. Y. A.; Ahmed, S.; Akhtar, S. (Engineering, Technology & Applied Science Research, 2018)
This paper is concerned with the investigation of a possible working principle of a microwave sensor for the measurement of water levels in plastic pipes. According to the research, most current sensors for water level measurement require an unobstructed path from the sensor in the water and therefore, the integrity of the pipes, in which water flows, will be compromised. The proposed sensor will work at microwave frequencies to measure the flow in the pipes from the outside. This would be non-invasive and non-intrusive. A beam of microwave energy from an antenna is directed towards a water surface within a pipe and the reflection due to the surface of the water will be isolated and knowledge of the pipe dimensions and properties will allow the depth of water to be calculated. Knowledge of the pipe drop may also allow flow to be estimated. It is observed that at microwave frequencies the reflection from the surface of the water is many times greater than the reflection from the surface of a typical plastic pipe.